Potential of Salt Tolerant PGPR in Growth and Yield Augmentation of Wheat (Triticum aestivum L.) Under Saline Conditions - Nawaz, Aniqa; Shahbaz, Muhammad; Asadullah,; Imran, Asma; Marghoob, Muhammad U.; Imtiaz, Muhammad; Mubeen, Fathia (Frontiers in Microbiology, 2020)
Soil salinity has been emerged as a major obstacle to meet world food demands. Halo-tolerant PGPR are potential bioinoculants to enhance crop productivity in saline agriculture. Current work was aimed to study individual or synergetic impact of salt tolerant PGPR on wheat growth and yield under saline conditions. Pot experiment conducted on two wheat genotypes (Aas-11; salt tolerant and Galaxy-13; salt sensitive) inoculated with P. fluorescence, B. pumilus and E. aurantiacum alone and in consortium. Salt tolerant variety (Aas-11) exhibited maximum root fresh (665.2%) and dry biomass (865%), free proline (138.12%) and total soluble proteins (155.9%) contents, CAT (41.7%) activity and shoot potassium uptake (81.08%) upon inoculation with B. pumilus, while improved shoot dry weight (70.39%), water (23.49%) and osmotic (29.65%) potential, POD (60.51%) activity, enhanced root potassium (286.36%) and shoot calcium (400%) were manifested by Ex. aurantiacum. Highest shoot length (14.38%), fresh weight (72.73%), potassium (29.7%) and calcium (400%) acquisition as well as glycinebetaine (270.31%) content were found in plants treated with PGPR consortium. On the other hand, in salt sensitive variety (Galaxy-13), P. fluorescence treated plants showed significantly improved leaf water relations, glycinebetaine (10.78%) content, shoot potassium (23.07%), root calcium (50%) uptake, and yield parameters respectively. Plant root length (71.72%) and potassium content (113.39%), root and shoot fresh and dry biomass, turgor potential (231.02%) and free proline (317.2%) content were maximum upon PGPR inoculation in consortium. Overall, Aas-11 (salt tolerant variety) showed significantly better performance than Galaxy-13 (salt sensitive variety). This study recommends B. pumilus and E. aurantiacum for salt tolerant (Aas-11) and P. fluorescence for salt sensitive (Galaxy-13) variety, as potential bioinoculats to augment their growth and yield through modulation of morpho-physiological and biochemical attributes under saline conditions.